2020
DOI: 10.1007/s11340-020-00584-7
|View full text |Cite
|
Sign up to set email alerts
|

Fracture and Cohesive Parameter Identification of Refractories by Digital Image Correlation Up to 1200°C

Abstract: The mechanical and fracture properties of refractory ceramics are determined by means of an inverse identification procedure between experimental data and numerical simulations. An experimental set-up is proposed to perform Wedge Splitting Tests (WST) at elevated temperature with Digital Image Correlation (DIC) to assess the crack propagation. The ceramic Young's Modulus, fracture energy and strength are determined by indirect confrontation to Finite Element simulations of crack propagation in WST specimens em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…In addition to the strength and fracture toughness, required as inputs, a third parameter intervines in CZM: The traction-opening displacement profile. This parameter mainly has an influence on dynamic phenomena such as crack initiation [28,44,45], crack branching or unstable propagation [28,46], whereas similar results are obtained whatever the chosen profile in case of stable rectilinear crack propagation [45,46] provided the characteristic length is small with respect to the specimen dimensions.…”
Section: Cohesive Zone Modelingmentioning
confidence: 89%
“…In addition to the strength and fracture toughness, required as inputs, a third parameter intervines in CZM: The traction-opening displacement profile. This parameter mainly has an influence on dynamic phenomena such as crack initiation [28,44,45], crack branching or unstable propagation [28,46], whereas similar results are obtained whatever the chosen profile in case of stable rectilinear crack propagation [45,46] provided the characteristic length is small with respect to the specimen dimensions.…”
Section: Cohesive Zone Modelingmentioning
confidence: 89%
“…A first case in which the Crack Mouth Opening Displacement (CMOD) was measured from images of MgO-C samples in WSTs up to 1500°C was reported by Brochen et al [41]. Moreover, to the authors' best knowledge, only one work reported WSTs analyzed with full-field measurements via DIC at a temperature of 1200°C) [42] on a commercial refractory for the calibration of a cohesive zone model. Pan et al [43] studied through WSTs the influence of different sintering temperatures on the fracture energy evaluated at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The same models may also be used to study interface cohesion in such heterogeneous materials [14,15,16]. More recently, several examples are found about its usage to simulate initiation and propagation of macrocracks [17,18,19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, inverse algorithms were used to find the best fit of the loading curve [18,19]. Vargas et al [20] used measured CMODs to prescribe boundary conditions and used the force measurements in the cost function of a Finite Element Model Updating (FEMU) procedure, while Doitrand et al [21] also used force measurement and crack lengths estimates to find the best fit through manual optimization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation